Microsoft Word 97 for Windows 95 - Murphy, Patricia (DDC Pub., 1998)
Microsoft Word '97 QuickTorial provides a complete learning package that makes the mastery of software applications both easy and fun. Designed to get you up and running quickly, Microsoft Word '97 QuickTorial allows users to master computer tools with a minimum of time and effort. With numerous screen illustrations and lots of hands-on activities for guidance, you learn quickly in a straightforward, understanding manner. The section on Webtop Publishing with Word allows users to take advantage of Microsoft Word 97's new Internet capabilities